Deallergisation trials of pure celery juice and apple-celery juice mixture by oxidation - Pavla Novotná; Ivana Šetinová; Martina Heroldová; Milena Kmínková; Jiřina Průchová; Jan Strohalm; Vlasta Fiedlerová; Renata Winterová; Petr Kučera; Milan Houška (Czech Journal of Food Sciences, 2011)
This work aimed to determine if it was possible to eliminate or reduce the content of the Api g1 allergen in celery juice by oxidation, utilising its natural polyphenol oxidase (PPO) content. We attempted to determine a possible relationship between the enzymatic browning of celery juice and the reactivity of the Api g1 allergen. Pressed celery juice was stirred, and samples for the colour measurement and allergenicity, determined using the Western Blot (WB) method, were collected at pre-defined times. Oxidation failed to eliminate the allergenicity of pure celery juice. Further trials were focused on celery allergen elimination in apple-celery juices mixtures in ratios of 3:1, 5:1, and 7:1. We selected the 5:1 ratio as the most acceptable from the sensory perspective, and monitored its allergenicity using the WB method, basophil activation test, and skin prick testing. The WB test showed that oxidation, caused by stirring for 120 min, reduced the allergenicity of the mixture. However, the basophil activation test showed no reduction in the allergic response to the oxidised juice mixture. Skin testing showed that the oxidised juice mixture stirred for 120 min exhibited a significantly lower reaction than the juice mixture stirred for 60 min or celery and apple juice stabilised with ascorbic acid. Due to the contradictory results in different tests, the method cannot be declared successful or safe, even for mixtures of apple-celery juices.